Acute and Subchronic Toxicities of Indonesian Mistletoes Dendrophthoe pentandra L. (Miq.) Ethanol Extract - Resmi Mustarichie, Sohadi Warya, Nyi Mekar Saptarini, Ida Musfiroh (Journal of Applied Pharmaceutical Science, 2016)
Traditionally mistletoes Dendrophthoe pentandra (L.) Miq known in Indonesia is to cure cough, hypertension, diabetes, cancer, ulcers, smallpox, diuretic, skin infection and after child-birth. The objective of this study was to evaluate the toxic effects at short and long term the Dendrophthoe pentandra ethanol extract in mice. In the acute test, the limit test dose of 40 g/kg of aqueous and hydroalcoholic extracts were administered orally to mice and then observed individually 2 h post-dosing and at least once daily for 14 days. Sub-chronic toxicity was evaluated after a daily oral administration of 420 mg/kg in a suspension of 2 % PGA for 90 days to Wistar rats. Animals were sacrificed and their organs were examined. The results showed LD50 values for acute toxicity at a dose of 17.78 and 12.59 g/kg which was comparable to a dose of 12.45 g/kg and 8.81 g/kg in rats. From the subchronic, the values of the parameters of hemoglobin, hematocrit, leukocytes, and erythrocytes index were still within the range of the reference. From histopathological examination value, the results revealed some abnormalities. Our results suggest the ethanol extract of Dendrophthoe pentandra have LD50 values which have practically not toxic but is not recommended to be used for a long periode.
Keywords: Ethanol extract, Dendrophthoe pentandra, acute toxicity, subchronic toxicity, mice.